The Correlation Between Garim's Competency-Based Educational Empowerment and Community Worship Levels at The Mosque in Kapa Village - Yudistira, Fernando; Dusni, Sari; Sinaga, Yeni Yasyah (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2025)
This study aims to describe and analyze in more depth the correlation between empowerment of gharim competency education and the level of worship of mosque communities in Kanagarian Kapa, West Pasaman Regency, West Sumatra Province. The research method used is descriptive qualitative aimed at creating a systematic, factual and accurate description, picture of the facts, characteristics and relationships between the social phenomena studied. Data collection was carried out through observation, interviews and documentation. Data analysis using Data analysis using data reduction techniques, data presentation, and drawing conclusions. Data validity using triangulation techniques and sources. The results of the study showed that the correlation of empowerment of gharim competency education and the level of worship of mosque communities was very significant. The gharim competency education related to cleanliness applies five important points: 1) cleaning glass, mosque floors regularly; 2) maintaining the cleanliness of mosque carpets; 3) rearranging mukena, sarongs and the Qur'an; 4) maintaining the cleanliness of ablution places and toilets; 5) cleaning dust on mosque shelves and mosque ceilings. The empowerment materials of competency skill education are as follows: 1) Azan and iqamah, 2) Sermon, 3) Tilawah, 4) Lecture. This research is able to be a stimulator of increasing self-potential and professionalism of gharim performance significantly and has a correlation with increasing worship of the mosque community significantly so that this community service research has great potential to be applied in other areas.